Supervision of Instructional Programmes for Improving Students ’ Performance in Secondary Schools in Tanzania - Urio, Perpetua (Papers in Education and Development, 2016)
This paper explores leadership practices in supervising instructional programmes for improving students ' performance in secondary schools. This study was conducted in four secondary schools with the two categories of best performing and worst performing schools in Morogoro Region, using a sample of fifty-nine respondents. The study used the qualitative approach. Data were collected through interviews, focus group discussion, documentary review and observation, and were later subjected to content analysis. The study findings revealed that the leaders of best-performing schools were able to manage instructional programmes through timely planning and monitoring students ' performance. The worst performing schools did not supervise teachers during classes nor did they have a way for holding teachers responsible for their performance. Teachers were rewarded according to the job well done, especially in how students performed in national examinations. The quality assurance office should concentrate on improving the instructional supervision of school heads and other leaders and create harmonious relationships to support schools in improving their performance. Similarly, the school leadership should be assisted in establishing and implementing a clear way for holding teachers and other staff responsible for their performance. Key words: Accountability mechanisms, instructional leadership, school leadership, instructional supervision,